Short Communication: Decreased populations of Scutellaria discolor and Plectranthus galeatus (Lamiaceae) on Mount Gede, West Java, Indonesian and its surrounding - SUDARMONO SUDARMONO (Biodiversitas Journal of Biological Diversity, 2018)
Sudarmono. 2018. Decreased populations of Scutellaria discolor and Plectranthus galeatus (Lamiaceae) on Mount Gede, West Java, Indonesian and its surrounding. Biodiversitas 19: 1866-1870. Scutellaria discolor Colebr. and Plectranthus galeatus Vahl. are herbs belonging to mint family (Lamiaceae) which have the potential to be used for medicinal purposes. However, their population is gradually declining. The population of the two species are now only found in the mountains or highlands or the edges of the forests that are still protected, i.e. Mount Gede and Telaga Warna protected forest. This research aimed to know the condition of parent and seedling population of Scutellaria discolor Colebr and Plectranthus galeatus Vahl. on Mount Gede and Telaga Warna vicinities, West Java Province, Indonesia. The research method used was parallel transect lines. Association of the existing plants in the vicinity of the area were also observed. In Mount Gede at altitudes about 1200 m above sea level there are 203 seedlings and 167 parents of S. discolor species, while there are 69 seedlings and 11 parents of P. galeatus. This is higher than the populations of 1100 m altitude, i.e. there are 76 seedlings and 45 parents of S. discolor and 12 seedlings and 9 parents of P galeatus. In Telaga Warna, S. discolor exist only at altitudes about 1500 m asl., i.e.. 47 seedlings and 52 parents. While for P. galeatus, there are 37 seedlings and 31 parents at altitudes about 1500 m. At altitude below 1400 m, there are 18 seedlings and 8 parents, this is very rare. Populations of S. discolor and P. galeatus in Mount Gede at an altitude between 1100-1300 m asl is a balance between the seedlings and its parent population which is the same for seedling populations of S. discolor in Telaga Warna at an altitude of 1400-1500 m asl, but for P. galeatus seedling number decreases from an altitude of 1400 to 1500 m asl.